Profile of Patients’ Osteoarthritis at Tertiary and Teaching in Aceh, Indonesia - Alex Kurniawan Gan; Armia Indra Nur Alam; Safrizal Rahman; Bellinda Paterasari (Surabaya Physical Medicine and Rehabilitation Journal, 2023)
Background: Osteoarthritis is a degenerative joint disease characterized by damage of cartilage in the joints and subchondral bones that cause pain in a joint. Aim: To describe the patients’ profile of osteoarthritis at the Dr Zainoel Abidin Hospital Banda Aceh. Material and Methods: A retrospective observational descriptive study on osteoarthritis patients who were treated at the Orthopaedic Clinic of RSUDZA Banda Aceh for the period March 2020 to February 2022. Results: Two years of observation yielded a total of 397 osteoarthritis patients. Most cases are in female patients (63.4%), with the majority of those in the age bracket >55 years (61.9%), with the majority of patients being from Banda Aceh City (37.2%). The most diagnoses are knee OA, which is 330 patients (82.9%) and hip OA, which is 39 patients (9.9%). Only 108 patients received surgery, operations for knee OA, total knee replacement were 78 patients (23.63%), while for hip OA patients who needed total hip teplacement surgery there were were 26 patients (66.66%) and partial hip replacement was 4 patients (10.25%). Conclusion: Osteoarthritis often occurs in female patients and mostly in the patient age group >55 years. Indications for surgery in OA are based on symptoms, stage of OA, and patient-related factors such as age, level of physical activity, and patient comorbidities.